EFFICACY OF THE METABOLIC DRUGS IN THE TREATMENT OF PATIENTS WITH STABLE ANGINA III FC AND HYPERTENSION - Зозуляк, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Considering the high prevalence of comorbid pathology Coronary Artery disease and Hypertension, an extremely important is the search of the treatment optimization of these patients to reduce complications, disability of the population and fatal consequences. Usually the treatment of comorbid pathology is focused on hemodynamic part of the cardiovascular system, but such drugs do not protect myocardial cells from ischemic changes. The aim of the study was to increase effectiveness of treatment of the patients with Stable Angina with Hypertension by potentiation of antianginal activity of prolonged nitrates on the background of therapy with basic drug and metabolic drugs mexicor, or tivortin, or combination of both. Material and methods. It was observed 125 patients with Stable Angina FC III and Hypertension. The effectiveness of the treatment was assessed by the dynamics of clinical signs and tolerance to physical activity. The results and conclusions. The result of the study showed that the most effective according to the potentiation of antianginal therapy of nitrates was combined use of mexicor and tivortin on the background of basic therapy. The results allow to recommend mexicor and tivortin as a means of basic therapy potentiating the antianginal efficiency of nitrates.